Three-dimensional inversion of corona structure and simulation of solar wind parameters based on the photospheric magnetic field deduced from the Global Oscillation Network Group - Zhang, Xiao; Qiu, Shican; Soon, Willie; Yousof, Hamad (Frontiers in Astronomy and Space Sciences, 2023)
In this research, the Potential Field Source Surface–Wang–Sheely–Arge (PFSS–WSA) solar wind model is investigated. This model consists of the Potential Field Source Surface (PFSS) coronal magnetic field extrapolation module and the Wang–Sheely–Arge (WSA) solar wind velocity module. PFSS is implemented by POT3D package deployed on Tianhe 1A supercomputer system. In order to obtain the three–dimensional (3D) distribution of the coronal magnetic field at different source surface radii (Rss), the model utilizes the Global Oscillation Network Group (GONG) photospheric magnetic field profiles for two Carrington rotations (CRs), CR2069 (in 2008) and CR2217 (in 2019), as the input data, with the source surface at Rss=2Rs, Rss=2.5Rs and Rss=3Rs, respectively. Then the solar wind velocity, the coronal magnetic field expansion factor, and minimum angular distance of open magnetic field lines from the coronal hole boundary are estimated within the WSA module. The simulated solar wind speed is compared with the value for the corona extrapolated from the data observed near 1 AU, through the calculations of the mean square error (MSE), root mean square error (RMSE) and correlation coefficient (CC). Here we extrapolate the solar wind velocity at 1 AU back to the source surface via the Parker spiral. And the effect of Rss on these physical parameters is analyzed by tuning all combinations of simulations.